Urethral Diverticulum Calculi in a Male: A Case Report - Gadimaliyev, Emil (Hindawi Publishing Corporation, 2013)
A 42-year-old male presented to the urology department, complaining of frequency and dysuria. A large number of calculi were revealed on IVU and USS. On endoscopic investigation, there were 3 stones (1.5 × 1 cm) found in the bladder and 5 more (1.5 × 0.8 cm) in the diverticulum of the posterior urethra. All of the stones were successfully broken down via a transurethral approach. This paper contains a detailed description of the case.